Brain stimulation treatments in bipolar disorder: A review of the current literature. (2nd October 2016) - Oldani, Lucio; Altamura, A. Carlo; Abdelghani, Mohamed; Young, Allan H.
Abstract : Objectives. Brain stimulation techniques are non-pharmacologic strategies which offer additional therapeutic options for treatment-resistant depression (TRD). The purpose of this paper is to review the current literature regarding the use of brain stimulation in resistant bipolar disorder (BD), with particular reference to hypomanic/manic symptoms. Methods. Keywords pertaining to the brain simulation techniques used in the treatment of depression (either unipolar or bipolar) along with their role in regard to hypomanic/manic symptoms were used to conduct an electronic search of the literature. Pertinent findings were identiﬁed by the authors and reviewed. Results. Brain stimulation techniques represent a valid therapeutic option in TRD. They have been extensively studied in unipolar depression and, to a minor extent, in the depressive phase of BD, showing encouraging but often limited results. With exception of electroconvulsive therapy, the efficacy of brain stimulation in the treatment of manic symptoms of bipolar patients is still uncertain and needs to be fully evaluated. Conclusions. Brain stimulation in BD is derived from its use in unipolar depression. However, there are many important differences between these two disorders and more studies with a systematic approach need to be conducted on larger samples of bipolar patients with treatment-resistant characteristics.